Principles of endoluminal therapy. Issue 6 (June 2018) - Brooks, Marcus; Hardman, John
Abstract: This article provides an overview of the diagnostic and therapeutic roles of endoluminal therapy in vascular disease. The emphasis is on techniques for safely achieving arterial access, navigation through vessels and arterial closure. Non-invasive arterial imaging is the key to successful planning of endovascular procedures. Therapeutic endovascular procedures including angioplasty, stenting, embolization, thrombolysis, endovenous therapies and endovascular aortic aneurysm repair will be described. New technologies include drug-coated balloons and stents (DCBs/DESs) and intravascular ultrasound (IVUS). The changing role of endovascular aneurysm sealing (EvAS) is discussed.